TRADITIONAL USE OF RORANO FOR POSTPARTUM RECOVERY AMONG THE TERNATE COMMUNITY - Masita Hariyanto; Sarni J Ishak (Journal of Midwifery Science and Women's Health, 2026)
Indonesia is a country with the second-highest biodiversity after Brazil, with more than 1,000 plant species identified as potential sources of medicinal ingredients used by the Indonesian people, including in Ternate City, North Maluku. In Ternate, postpartum recovery practices rely not only on medical services but also incorporate local knowledge passed down through generations. One such practice is the use of rorano, a traditional herbal remedy rooted in local wisdom, believed to accelerate healing and restore the stamina or health of postpartum mothers. Postpartum recovery is a crucial phase in the female reproductive health cycle. This traditional herbal remedy, based on the local wisdom of Ternate’s believed to accelerate the reduction of Fundal Height (FH), the expulsion of blood and placental remnants, eliminate postpartum odor, and reduce afterpains. To explore the practice of using rorano and its benefits for postpartum mothers in the Ternate community, identify the composition of ingredients, processing methods, and community perceptions of the role of rorano in postpartum care in the city of Ternate. The method used is a qualitative approach with a case study design. Based on the interview result in this study, 15 respondents reported knowing about rorano, the ingredients used in rorano are classified as Family Medicinal Plants (TOGA), the most commonly used ingredients by the community include miana leaf extract (Coleus atropurpureus.), daun beluntas  (Pluchea indica.), purple leaves (Graptophyllum pictum L. Griff), Insulin leaves (Costus Igneus), turmeric (Curcuma longa L.), and nutmeg seeds (Myristica Fragnans Houtt)